Contracts in Offshore Software Development: An Empirical Analysis - Gopal, Anandasivam; Sivaramakrishnan, Konduru; Krishnan, M. S.; Mukhopadhyay, Tridas (Management Science, 2003)
We study the determinants of contract choice in offshore software development projects and examine how the choice of contract and other factors in the project affect project profits accruing to the software vendor. Using data collected on 93 offshore projects from a leading Indian software vendor, we provide evidence that specific vendor-, client-, and project-related characteristics such as requirement uncertainty, project team size, and resource shortage significantly explain contract choice in these projects. Our analysis suggests that contract choice significantly determines project profit. Additionally, some ex ante vendor-, client-, and project-related characteristics known at the time of choosing the contract continue to significantly influence project profits after controlling for contract choice. We also provide evidence to show that project duration and team size affect project profits.